Mirror Syndrome after Fetoscopic Laser Treatment - A Case Report - Ana Maria Simões Brandão; Ana Patrícia Rodrigues Domingues; Etelvina Morais Ferreira Fonseca; Teresa Maria Antunes Miranda; José Paulo Achando Silva Moura (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Mirror syndrome is a rare disease with unknown pathophysiology that can be present in different diseases that can cause fetal hydrops. The prognosis is usually bad with a high perinatal mortality. We report an unusual form of mirror syndrome that manifested itself only after a successful treatment for fetal hydrops (caused by twin-twin transfusion syndrome, in Quinteros stage IV) was performed. This syndrome was controlled by medical treatment, and despite the usually bad prognosis seen in these cases, we could extend the pregnancy from the 23rd to the 34th week of gestation, resulting in the birth of 2 live infants.